Methane production from acidic effluent discharged after the hydrogen fermentation of sugarcane juice using batch fermentation and UASB reactor. (February 2016) - Reungsang, Alissara; Sittijunda, Sureewan; Sreela-or, Chakkrit
Abstract: Acidic effluent discharged after the hydrogen fermentation of sugarcane juice was used to produce methane by batch fermentation and UASB reactor. Significant parameters affecting methane production including substrate to biomass (S/X) ratio, nickel (Ni) concentration, and cobalt (Co) concentration were optimized by response surface methodology with central composite design in batch mode. A maximum methane yield (MY) of 305.4 mL CH4 /g-volatile solid (VS)substrate (sub)-added was achieved at an S/X ratio of 0.83 g-VSsub /g-VSinoculum, a Ni concentration of 0.53 mg/L, and a Co concentration of 0.06 mg/L. Continuous methane production was conducted at various hydraulic retention times (HRT) using the optimum conditions obtained from the batch experiments. The optimum HRT of 4 days in a UASB reactor resulted in a maximum methane production rate (MPR) and MY of 1.27 ± 0.05 L-CH4 /L-culture day and 348 ± 13 mL-CH4 /g-COD, respectively. Total energy generated was 219.23 kJ/L-substrate or 8.77 kJ/g-COD, and COD removal efficiency was 75.60%. Highlights: Effluent after hydrogen production of sugarcane juice was used to produce methane. RSM with CCD was used to optimize the key parameters in batch fermentation. 0.83 g-VSsub /g-VSinoc of S/X, 0.53 and 0.06 mg/L of Ni and Co gave the highest MY. Optimum HRT of 4 days in UASB reactor gave a maximum MY of 1348 ± 13 mL-CH4 /g-COD. Total energy generated was 8.77 kJ/g-COD and COD removal efficiency was 75.60%.